Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1007/s11842-010-9125-z
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Cautious: Israel’s Afforestation Experience and Approach to Sequestration

Abstract: During the past 60 years, afforestation has transformed Israel's landscape, with forests planted or planned on 10% of the country's land, much of it with less than 300 mm of annual precipitation. After early efforts to establish a successful commercial timber industry failed, recreation and ecosystem services came to dominate forestry policy objectives. Given Israel's status as a 'developing country' under the Kyoto Protocol, forests' economic potential through carbon sequestration has been explored, but has n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 36 publications
1
14
0
Order By: Relevance
“…High transaction and establishment costs balanced out the benefits from tCER, as was previously observed in the review of existing CDM A/R projects (Thomas et al, 2010). Based on the case of dryland afforestation in Israel, similar conclusions were derived by Tal and Gordon (2010) who indicated that, under the present prices of CER, the costs of registration and monitoring were likely to prohibit participation in small-scale CDM A/R. The introduction of suitable CDM methodologies, which have increased in number during recent years, could reduce transaction costs for new projects.…”
Section: Estimation Of Tcer Valuesupporting
confidence: 66%
See 1 more Smart Citation
“…High transaction and establishment costs balanced out the benefits from tCER, as was previously observed in the review of existing CDM A/R projects (Thomas et al, 2010). Based on the case of dryland afforestation in Israel, similar conclusions were derived by Tal and Gordon (2010) who indicated that, under the present prices of CER, the costs of registration and monitoring were likely to prohibit participation in small-scale CDM A/R. The introduction of suitable CDM methodologies, which have increased in number during recent years, could reduce transaction costs for new projects.…”
Section: Estimation Of Tcer Valuesupporting
confidence: 66%
“…While some studies concluded that present policies have encouraged tree planting as a climate change mitigation option (e.g., Parks and Hardie, 1995;Niu and Duiker, 2006), others have claimed that such projects could be attained only at a significant cost and would require a substantial change in the present climate agenda regulations (e.g., van Kooten, 2000;Krcmar et al, 2005;Tal and Gordon, 2010). On-going debates in forestry studies have not conclusively resolved the concern over determining the price for C stored in wood.…”
Section: Introductionmentioning
confidence: 99%
“…We roughly estimated the cost for capability development, including fodder production and biogas technology transfer and workshops for land-use planning, at $298,100 (Teune 2007;JICA 2008), which finally increased the emission reduction cost to $26.3/tCO 2 . It is difficult to expect this additional cost to be borne by carbon investors under the current A/R CDM system (Harvey et al 2010), where project financing depends completely on market mechanisms and the carbon credit from A/R CDM projects is tended to be low in the market (Tal and Gordon 2010). It is highlighting the need for a new funding source for development of A/R CDM readiness before project implementation.…”
Section: Additional Project Cost and Funding Source Of Capability Devmentioning
confidence: 99%
“…Especially, it has been found that the low price of expiring temporary credits and the complex rules are major constraints (Rocha 2008;Streck et al 2009b;Lasco et al 2010;Tal and Gordon 2010). The expiring temporary credit was not attractive to carbon investors, and the price tended to be far lower than for other carbon emission reduction projects (Tal and Gordon 2010).…”
mentioning
confidence: 99%
“…After twenty years, many reasons can be given as to why the UNCCD has failed to achieve meaningful progress at the global level among countries affected by desertification. On the one hand, affected countries have not provided the "top-down" guidance that land managers and farmers needed to prevent land degradation (Tal, Gordon, 2010). The UNCCD was not successful in facilitating the integration of its objectives into existing or new national development plans whose provisions may even exacerbate the problem of land degradation (Stringer, 2008).…”
mentioning
confidence: 99%